ALTERATIONS IN GONADAL OXIDATIVE STRESS MARKERS AND REPRODUCTIVE FUNCTION OF BALB/c MICE INFECTED WITH MALARIA PARASITE, PLASMODIUM BERGHEI (Nigerian Journal of Physiological Sciences, 2019)
In this study, the changes in gonadal oxidative stress markers and reproductive function of BALB/c mice were investigated. Forty-eight (48) BALB/c mice acquired for this study were randomly divided into four groups of eight mice each. Each group was further sub-divided into male and female groups with equal number of mice. The groups were represented as thus: Group A: normal mice; Group B: mice infected with malaria parasite, Plasmodium berghei; Group C: malaria infected mice treated with Artemether/Lumefantrine; Group D: malaria infected mice treated with Vitamin E. The experimental mice were inoculated with the Plasmodium bergehi, and the malaria parasite were confirmed in the mice four days later before the commencement of the experiments. After the experimental procedures which lasted for fourteen (14) days, the mice were sacrificed, blood samples collected for serum testosterone, estrogen and progesterone assay; semen were collected for semen analysis; and testes and ovaries were harvested for histological analysis and oxidative stress marker determination. Result show that malaria parasite, Plasmodium berghei significantly (p